Acute Toxicity of Leachates from Water Treatment Plants Sludge and Combinations with Soils from a Tropical Region - Rodgher, Suzelei [UNESP]; Fiore, Fabiana Alves [UNESP]; dos Santos Bardini, Vivian Silveira; Formiga, Jorge Kennety Silva [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Klinsky, Luis Miguel Gutiérrez (My University, 2023)
Sludge from water treatment plants (WTP) is a waste of continuous and increasing generation, with a polluting potential associated with the composition of water source and the inputs used in the potabilization process. Currently, most of these residues are released in natura into aquatic systems, which motivates research related to the beneficial use of the material, especially incorporations with soils in geotechnical works. This study evaluated the toxicity of WTP sludge leachate and its combinations with soils from the State of São Paulo (Brazil) using cladoceran Daphnia similis, a standardized test species in tropical aquatic environments. For that, acute toxicity tests were carried out with D. similis testing leachate from twelve different compositions of aluminum and iron sludge and sandy soils and clayey sand. The concentrations of Fe and Al (dissolved) and Ba, Mn and Cl (total) present in the leachate from these samples were determined. Among the main results, it is highlighted that all the raw leachates samples caused 100% immobility for D. similis, and the toxicity of the samples varied according to the chemical elements detected and the type of soil used.
Keywords: Daphnia similis; Ecotoxicity; Sludge disposal; Waste reuse